Facial Reconstruction of a Mucormycosis Survivor by Free Rectus Abdominis Muscle Flap, Tissue Expansion, and Ocular Prosthesis. Issue 6 (November 2016) - Silberstein, Eldad; Krieger, Yuval; Rosenberg, Nir; Bogdanov-Berezovsky, Alexander; Shoham, Yaron; Saphier, Oshra; Pagkalos, Vasileios A.; Joshua, Ben-Zion
Abstract : Invasive sinonasal mucormycosis is a rare fungal infection that usually occurs in immunocompromised or diabetic patients, and it is often fatal. The authors present a case of a woman patient suffering from systemic lupus erythematosus and diabetes mellitus treated with prednisone, presenting with a rapidly progressive rhino-orbital-cerebral mucormycosis. She was successfully treated with combined intravenous antifungal therapy and radical debridement followed by complex defect reconstruction with a free vertical rectus abdominis myocutaneous flap, tissue expander, and ophthalmic prosthesis. Abstract : The authors present a case of rhino-orbital-cerebral mucormycosis that was successfully reconstructed with a free vertical rectus abdominis myocutaneous flap, tissue expander and ophthalmic prosthesis.